Systematic studies on behaviors of ultra-high performance concrete subject to freezing and thawing cycles combining DIC technology - Wang, Fei; Kan, Lili; Yu, Jiangtao; Duan, Xin-Zhi (Construction & building materials, 2023)
•Combination of destructive and non-destructive tests are used to valuate UHPC frost-resistance.•Tensile properties, flexural and compressive strength under different freezing and thawing cycles were investigated.•The strain and strength indices are adopted to explain the magnitude of tensile strain capacity.•Digital image correlation technology is applied to analyze the cracking behaviors. Freezing and thawing alternation is one harsh weather condition for the concrete structures serving in seasonal frozen areas. As an emerging construction material, the frost-resistance of ultra-high performance concrete (UHPC) is highly necessary to be understood for propelling its practical application. In this study, the frost-resistance of UHPC was systematically evaluated based on the mechanical properties and the cracking behaviors. The fast freezing and thawing (FT) cycles were chosen as the experiment condition, along with the water-immersion condition for comparison. A combination of destructive mechanical and non-destructive resonance frequency test was used to characterize the behaviors. The results showed that, after undergoing 300 FT cycles, the tensile initial cracking strength, the tensile strength, the flexural strength, and the compressive strength exhibited a certain of degradations. The corresponding effects of the water-immersion action were more positive. The tensile strain capacity under the FT condition almost kept constant, whereas that under the water-immersion condition decreased. The two indices (including strain and strength) could reasonably reflect the magnitude of tensile strain. The digital image correlation (DIC) analysis unveiled that there may exist an additional plastic deformation in the tensile full-field deformation, apart from the elastic deformation and crack opening. Compared with the water-immersion action, the FT action resulted in a less zigzag cracking path, shorter cracking time, and larger crack opening under flexural loading. In addition, the variations of dynamic modulus of elasticity and re-hydration reaction degree under the FT condition were not coincident with those of mechanical properties. The findings could provide some valuable references for estimating the bearing capacity of the UHPC structures served in practical engineering.